'Walk This Way' – a pilot of a health coaching intervention to reduce sedentary behaviour and increase low intensity exercise in people with serious mental illness: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Williams, Julie; Stubbs, Brendon; Gaughran, Fiona; Craig, Tom
Abstract Background People with serious mental illness (SMI) (psychosis, bipolar disorder and major depressive disorder) experience a considerable risk of premature mortality because of cardiovascular disease. Recent research has demonstrated that this population spends almost 13 h per day being sedentary. Sedentary behaviour is an independent risk factor for cardiovascular disease and mortality. Given the potential for physical activity to improve health and well-being in people with SMI, we developed a pilot randomised controlled trial (RCT) to evaluate a coaching intervention aimed at reducing sedentary behaviour and increasing physical activity in people with SMI. Our primary aim was to assess the acceptability and feasibility of the intervention. Secondary aims were to see if the Walk This Way (WTW) intervention decreased sedentary behaviour and increased activity levels. Methods/design People with SMI who met any of the following criteria were recruited by two community mental health teams in South London: (1) overweight, (2) at risk for or have diabetes, (3) smoke tobacco or (4) have a sedentary lifestyle. Care co-coordinators (clinical case managers) identified potentially eligible participants within their caseload, and these individuals were subsequently invited to participate. All participants' physical activity (self-reported and accelerometer-recorded), health status (including metabolic blood tests) and motivation to exercise were assessed at baseline. Participants were randomised to receive treatment as usual or the WTW intervention. WTW consisted of an educational intervention at baseline on the benefits of an active lifestyle. Participants were then given a pedometer and received fortnightly coaching from a staff member trained in coaching skills to help them to set daily walking targets, and they were invited to a weekly walking group. The WTW intervention lasted 17 weeks in total. Discussion To our knowledge, WTW is the first RCT to investigate the impact of a health coaching intervention targeting sedentary behaviour in people with SMI. It is hoped that if the intervention is feasible and acceptable, further large scale study can be developed and implemented in routine care. Trial registration ISRCTN37724980 . Registered on 4 Aug 2015.